1998
DOI: 10.1097/00000658-199801000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors After Repeat Hepatectomy for Recurrent Hepatocellular Carcinoma

Abstract: The only prognostic factor identified in patients with recurrent HCC after repeat hepatectomy was portal vein invasion in the first hepatectomy. Most second tumors after the first hepatectomy are considered to be caused by metastatic recurrence, not by multicentric occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
122
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 28 publications
6
122
2
Order By: Relevance
“…On the other hand, the Apo D expression values in tumor tissue specimens were significantly associated with the histological grade of the tumor, which is one of the most important prognostic factors for patients with HCC. [28][29][30] An immunohistochemical analysis also revealed a stepwise decrease in the expression at the protein level of well to moderately and poorly differentiated HCC. The prognosis of HCC patients with a low expression of Apo D was significantly worse than that in patients with a high expression.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the Apo D expression values in tumor tissue specimens were significantly associated with the histological grade of the tumor, which is one of the most important prognostic factors for patients with HCC. [28][29][30] An immunohistochemical analysis also revealed a stepwise decrease in the expression at the protein level of well to moderately and poorly differentiated HCC. The prognosis of HCC patients with a low expression of Apo D was significantly worse than that in patients with a high expression.…”
Section: Discussionmentioning
confidence: 94%
“…Since the presence of portal vein invasion is one of the most important prognostic factors for HCC patients (Izumi et al, 1994;Shimada et al, 1998;Ikai et al, 2004), we therefore investigated a possible correlation between EZH2 mRNA values, quantitatively determined by a real-time RT -PCR, and the prognosis of HCC patients. In the present study, however, we found no significant difference in the disease-free survival rate between the high expression group and the low expression group.…”
Section: Discussionmentioning
confidence: 99%
“…The liver accounts for 30%-91% of recurrent HCC and 40% of CRC metastases after surgery [18,[29][30][31] . The presence of satellite lesions, intrahepatic microvascular invasion and poor histological differentiation are markers for recurrence and a bad prognosis [11,32] .…”
Section: Characteristics Of Recurrent Liver Cancermentioning
confidence: 99%
“…The presence of satellite lesions, intrahepatic microvascular invasion and poor histological differentiation are markers for recurrence and a bad prognosis [11,32] . There are two distinct categories of recurrences: undetected micrometastasis due to multicentric tumor or "de novo" cancer arising as a result of an underlying carcinogenic liver disease in the liver remnant [11,30,31,33] . This distinction may have significant prognostic and therapeutic implications, but it can be difficult to make a differentiation between the two types in individual patients.…”
Section: Characteristics Of Recurrent Liver Cancermentioning
confidence: 99%